Child reading practices of Filipino urban mothers relationship to children's cognitive development - Razon, Perpetua G. Umali 1937-
The study investigated the child rearing patterns of Filipino urban mothers and the relationship of child rearing practices to the cognitive development of children. 150 mother-child pairs were used as subjects. Three child-rearing dimensions were used in the study: love-hostility, autonomy-control, and cognitive growth. It was concluded that Filipino urban mothers are loving yet controlling. They provide their children with varied activities for cognitive growth. Family structure, mother's work status, socio-economic status of the family and the sex of the child are not related to child rearing. The birth order of the child is related to child rearing practices of the mothers and to the cognitive performance of the child. Child rearing practice is significantly related to children's cognitive development